Antikitenin Öğrettikleri: Yeni Çağ Avrupa Düşüncesinde Yeni Stoacılık (Lessons From Antiquity: Neo-Stoicism In The Early Modern European Thought) - M. Burak Özdemir; Fatih Durgun (İnsan & Toplum)
Early Modern Europe witnessed the emergence of more centralised states as a consequence of socio-political, economic and religious turmoil. Since Renaissance and Reformation, it has been commonly held that Stoic philosophy has offered much more solid solutions to the problems of the crises in Western societies rather than the other philosophical schools of the Antiquity. This paper argues that the discourses shaped by references to the thinkers identified with Neo-Stoicism steered the course of intellectual discussions as well as political and intellectual programmes in this period. Besides, the place and influence of Neo-Stoicism, as an ancient philosophical school, in the formation of early modern central states should be emphasized.